2015
DOI: 10.1016/j.comppsych.2014.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Associations of working models of the self and other with Cloninger's personality dimensions

Abstract: The present study examined the associations of working models of the self and other, one of the key concepts of Bowlby's attachment theory, with the seven dimensions of Cloninger's personality model. The subjects were 542 healthy Japanese volunteers. Working models of the self and other were assessed by the Relationship Scales Questionnaire, and the seven dimensions of personality were evaluated by the Temperament and Character Inventory. In the correlation analysis, the self-model was correlated most strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“… 1 Also, these dimensions are closely related to working models of the self and other, which underlie and determine adult attachment styles. 34 Therefore, the present study indirectly supports the view that the mu-opioid receptor plays an important role in human attachment. 10 In this regard, our study is in line with that by Cimino et al 20 suggesting the importance of the OPRM1 polymorphism in human attachment.…”
Section: Discussionsupporting
confidence: 80%
“… 1 Also, these dimensions are closely related to working models of the self and other, which underlie and determine adult attachment styles. 34 Therefore, the present study indirectly supports the view that the mu-opioid receptor plays an important role in human attachment. 10 In this regard, our study is in line with that by Cimino et al 20 suggesting the importance of the OPRM1 polymorphism in human attachment.…”
Section: Discussionsupporting
confidence: 80%
“…Studies have shown that negative parenting practices from both parents are linked to stronger levels of schema domains [74,75]. ASs are also shaped by genetic factors, a child's temperament, and attachment experiences [76,77]. Some studies have found a positive relationship between authoritative parenting and secure attachment and negligent and authoritarian parenting, which predicted avoidant attachment [78].…”
Section: Parenting Style (Ps)mentioning
confidence: 99%
“…The psychobiological model of personality was initially developed for clinical assessment in both the general population and clinical settings, and it has proved to be an adequate framework for the description of both normal and abnormal human personality (Cloninger, Zohar, & Cloninger, 2010;Lee, Cloninger, Park, & Chae, 2015;Otani et al, 2015;Schneider, Ottoni, Carvalho, Elisabetsky, & Lara, 2015). In particular, recent studies have supported its suitability for describing the personality variables that underlie health behaviors and all components of subjective well-being, as well as ill-being, both in adults Josefsson et al, 2011;Zaninotto et al, 2016), and adolescents (Garcia et al, 2015;Moreira et al, 2015;Schu¨tz, Archer, & Garcia, 2013).…”
Section: Introductionmentioning
confidence: 99%